The consolidation and transformation of an ultra-ferritic stainless steel by hot isostatic pressing - Kian, Michael Christopher Wong. (My University, 1998)
Ferritic stainless steels possess a number of properties which render them superior to austenitic stainless steels in certain applications. The ferritic stainless steels are highly resistant to stress-corrosion cracking and are generally of lower cost. Previous work had shown that the corrosion properties of the ferritic steels were optimised at a chromium content of forty percent. Extensive research had already characterised the mechanical and corrosion behaviour of the Fe"40Cr alloy in the cast and wrought form. This investigation involves the development of the material by powder metallurgy processing. Particular emphasis is placed on a proprietary powder production technique as well as on powder consolidation by Hot Isostatic Pressing. The effect of Ni, Mo, Ru, Nb, Al and Fe additions and well as various techniques of introducing these additions are examined. The unique effect of powder metallurgy manufacture on microstructure and the kinetics of sigma phase formation is highlighted. Corrosion tests in various concentrations of sulphuric acid and an industrial field trial were performed. It was found that combined Ni and Mo contents exceeding four percent resulted in severe embrittlement due to widespread formation of sigma phase during the HIP process. The use of powder metallurgy techniques was also found to enhance the kinetics of sigma phase formation in a particular alley when compared to the as-cast state. Direct additions of Fe powder were successful in inhibiting embrittlement, possibly due to a mechanism of Fe diffusion into Cr-rich regions. This lowered of the Cr content in these regions, thereby reducing the tendency for sigma precipitation. Corrosion tests indicate satisfactory resistance for the Fc-40Cr-2Ni-2Mo alloys in 70 weight percent sulphuric acid at 50°C. Alloys with 0.2 percent Ru additions were found to be especially resistant, due to the role of Ru as a cathodic modifier. The method of mixing and diffusion bonding metallic powders of varying composition was found to be feasible and certain novel combinations of Ni and Fe-rich alloys exhibited satisfactory corrosion resistance. A mathematical diffusion model was found to provide an order of magnitude approximation of the time required for hornogentsation in a certain mixture of powders.
A dissertation submitted to the faculty of Engineering, University of the Witwatersrand, Johanuesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering.
Keywords: Ferritic steel.; Isostatic pressing.; Powder metallurgy -- Pressing.; Stainless steel.